Konseling Individual untuk Meningkatkan Kemandirian - Intan Murtafi’ah; Titin Swastinah; Sitti Ernawati (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2019)
Research on the delivery of services counseling sunday prologue an individual to increase of developing kind of confidence student of class viii at their own locations MTs. Al-Ma’Arif discerning men will vanish or Wuluhan academic year 2017/2018. With the treatment respondents as many as 32 students. Data collection methode used is observation and chief, analysis the data used was analysis data descriptive. The result of preliminary observations by giving chief and obtained data for main with the percentage level independence students at the school of 56%, after he received action against cycle in behavior independence students at the school as compete in terms of good judge confident, and responsibilities of increased with large percentage 65%, after continue to cycle in level behavior independence students increased with large percentage 81%. Thus obtained conclusion, service delivery individual counseling shows that behavior independence students at the school increased. Research activities have categorized successfully it reached the percentage above indicators success that has been set of 75 % the percentage independence students at the school. Therefore to service delivery individual counseling can increase independence students at the school class viii a in MTs. Al-Ma’arif Wuluhan academic year 2017/2018. Keywords: Counseling Individual, Independence